THE EFFECT OF PACKAGING ON CONSUMER BUYING INTEREST (CASE STUDY ON FOOD) UMKM POJOK SEPATAN - Mochamah Heru Riza Chakim; Mulyati Mulyati; Wiwin Winarti; Iyang Fatmawati (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
Damage to the packaging is a problem for entrepreneurs because the damage will result in reduced consumer confidence and interest in the product, this often occurs due to a lack of accuracy in product placement so that the packaging becomes damaged. On the other hand, this damage occurs because the packaging material does not match its contents, it can even occur because of the seller's negligence when putting the product in the packaging. This can be overcome by arranging packaging materials for products or goods so that they do not get damaged quickly and be careful when you want to wrap them, this research method uses a qualitative method. Many things are judged by a product, the packaging is a criterion in buying a product and packaging is also the main key for a company, sometimes it is not concerned with taste, only concerned with attractive packaging, and vice versa, even where consumers are concerned. these two things. Uniqueness is a challenge for companies in developing innovations and ideas to attract consumers with packaging. The basic concept of this research is to make packaging that is not easily damaged and attractive so that consumers are interested in the product. In Experimental Packaging, a new product to be released is getting a lot of positive opinions. This is the progress of the new product that will be issued by POJOK UMKM.